Motivation, Competence, Workload, and Their Association with Nurse Performance in Dr. Arif Zaenudin Hospital, Surakarta - Tia Martha Pundati; Didik Tamtomo; Endang Sutisna Sulaeman (Journal of Health Policy and Management, 2018)
Background: Nurses performance remains long standing determinates of quality service rendered for patients admitted to hospitals. Improvements in quality health service can be achieved by improving nurse performance. This study aimed to analyze the relationship of competence, motivation, and workload on the nurse performance in Surakarta.Subjects and Method: This was a cross sectional study conducted at Dr. Arif Zaenudin Mental Hospital, Surakarta, Central Java, from November 24 to December 24, 2017. A sample of 200 study subjects was selected by total sampling. The dependent variable is the nurse's performance, while the independent variables are competence, motivation, workload, employment status, education and the distance between the nurse's residence and the hospital. The dependent and independent variables were measured using a questionnaire. The data analysis was done using path analysis with the STATA 13 program.Results: The performance is influenced by competence (b= 1.08; 95% CI= 0.32 to 1.74; p= 0.005), motivation (b= 0.91; 95% CI= 0.15 to 1.68; p= 0.019), workload (b= 2.65; 95% CI= 1.91 to 3.40, p<0.001), there are 2 variables that have an indirect relationship with the nurse's performance, namely education (b= 0.67; 95% CI= -1.24 to -0.11; p = 0.019) and the distance of residence (b= -0.61; 95% CI= -1.20 to -0.20; p= 0.043).Conclusion: There is a direct relationship between competence, motivation, workload and work period with nurse performance. There is an indirect relationship between education and home distance with performance.Keywords: pathway analysis, competence, motivation, workload, performanceCorrespondence: